Establishment of cumulative assessment groups of pesticides for their effects on the nervous system. (17th September 2019) - ,; Crivellente, Federica; Hart, Andy; Hernandez‐Jerez, Antonio F; Hougaard Bennekou, Susanne; Pedersen, Ragnor; Terron, Andrea; Wolterink, Gerrit; Mohimont, Luc
Abstract: Cumulative assessment groups of pesticides have been established for five effects on the nervous system: brain and/or erythrocyte acetylcholinesterase inhibition, functional alterations of the motor, sensory and autonomic divisions, and histological neuropathological changes in neural tissue. Sources of uncertainties resulting from the methodological approach and from the limitations in available data and scientific knowledge have been identified and considered. This report supports the publication of a scientific report on cumulative risk assessment to pesticides affecting the nervous system, in which all uncertainties identified for either the exposure assessment or the establishment of the cumulative assessment groups are incorporated into a consolidated risk characterisation. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2019.EN-1702/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2019.EN-1708/full This publication is linked to the following EFSA Journal articles: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5764/full